2019
DOI: 10.3390/jmse7060165
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Assess the Stability of Unsaturated Multilayered Coastal-Embankment Slope during Rainfall Infiltration

Abstract: This study aims to develop a simple but effective approach to investigate the stability of an unsaturated and multilayered coastal-embankment slope during the rainfall, in which a Random Search Algorithm (RSA) based on the random sampling idea of the Monte Carlo method was employed to obtain the most dangerous circular sliding surface, whereas the safety factor of the unsaturated slope was calculated by the modified Morgenstern–Price method. Firstly, two typical distributions of matric suction were illustrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Coastal embankment is commonly used to property and safeguard human life from harsh environmental conditions like long-term wave loading, sea level rise, rainfall and storm [1]. One of the common problems faced at the embankment sites is erosion at the seaward slope.…”
Section: Formulation Of a Slope Protection Scheme For Senggarang Coas...mentioning
confidence: 99%
“…Coastal embankment is commonly used to property and safeguard human life from harsh environmental conditions like long-term wave loading, sea level rise, rainfall and storm [1]. One of the common problems faced at the embankment sites is erosion at the seaward slope.…”
Section: Formulation Of a Slope Protection Scheme For Senggarang Coas...mentioning
confidence: 99%
“…Their research suggests that coeval events (the strike-slip movement along the Red River Fault and the ridge jump of the South China Sea) in the Oligocene-Miocene boundary triggered the Baiyun-Liwan submarine slide. Zhu et al [16] developed a simple approach to investigate the stability of an unsaturated and multilayered coastal-embankment slope during the rainfall, in which a Random Search Algorithm (RSA) based on the random sampling idea of the Monte Carlo method was employed to obtain the most dangerous circular sliding surface, whereas the safety factor of the unsaturated slope was calculated by the modified Morgenstern-Price method. It was found that the fluctuation of the groundwater level has a significant influence on the location of the most dangerous sliding surface.…”
Section: Coastal Geohazardmentioning
confidence: 99%
“…(2) evaluation of stability of marine infrastructures, including pipelines [6][7][8], piled foundation and bridge piers [9][10][11][12], submarine tunnel [13], and other supported foundations [14]; and (3) coastal geohazard, including submarine landslide and slope stability [15,16] and other geohazard issue [17,18]. More details of each contribution are summarized in the following subsections.…”
Section: Introductionmentioning
confidence: 99%
“…traditional methods for slope stability analysis, such as limit equilibrium models and numerical modeling, have been effective but are often time-consuming and resource-intensive [3,4]. these methods have been applied in different parts of the world to analyze the impact of factors like rainfall on slope stability [5][6][7][8][9][10][11][12]. however, these methods struggle when dealing with complex and uncertain situations involving a multitude of interrelated factors.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies have contributed to our understanding of dump slope stability, they often focus on a limited set of parameters, neglecting crucial variables like weather conditions, blasting vibrations, and others [37][38][39][40]. in contrast to existing studies that often employ numerical modeling to understand the influence of rainfall on slope stability [6][7][8][9][10][11][12], this paper introduces machine learning to assess the stability of dump slopes in the presence of diverse external factors. A comprehensive analysis of 1620 cross-sections of existing dump profiles in indian mines was conducted.…”
Section: Introductionmentioning
confidence: 99%